Left-behind children's juvenile delinquency and substance abuse in China: policy examination and analysis - Hung, Jason (Springer, 2024)
"This book constructs the theoretical framework based on a range of prominent social theories to address how juvenile delinquency is socioeconomically constructed. Here the presentation of conceptual details is supported by Chinese literature that rationalises, problematises, and analyses how left-behind children are vulnerable to premature smoking, heavy drinking and drug abuse and. I critically review all the most recent publications to highlight the most updated socioeconomic structure of juvenile delinquency experienced by Chinese left-behind children. In addition, the author summarises and analyses all the most up-to-date policy recommendations and evaluations concerning the mitigation of left-behind childrens juvenile delinquency. The policymaking outputs help inform readers on how Chinese policymakers have specifically been endeavouring to intervene in left-behind childrens delinquent behaviours and what policy directions the corresponding policymakers are trending towards in the future." --